Novel dihydroxybenzohydrazide grafted deoxycellulose for efficient removal of anionic food colorants and hexavalent chromium from wastewater - Magda A. Akl; Azza A. H. Fahim; El-Sayed R. H. El-Gharkawy (Scientific Reports)
Abstract In this study, 2,4-dihydroxybenzaldehyde hydrazone (CELL@HBH) adsorbent was prepared from microcrystalline cellulose powder (CELL) through a simple and effective method. The investigated materials were characterized by Fourier Transform Infrared spectroscopy (FT-IR), Scanning electron microscopy (SEM), elemental analysis, Proton Nuclear Magnetic Resonance (1HNMR), Thermogravimetric analysis (TGA), X-ray diffraction (XRD), and Brunauer-Emmett-Teller (BET) surface area measurements. The prepared (CELL@HBH) adsorbent was applied to remove anionic food colorants carmoisine (E122), ponceau 4R (E124), and Cr(VI) from polluted water samples. The effects of pH, initial concentration, contact time, dosage, temperature, and competing ions have been investigated to maximize the adsorption capacities to reach 476.709 mg/g, 338.789 mg/g, and 190.072 mg/g for E122, E124, and Cr(VI) ions, respectively, at the optimum conditions. The results showed that the adsorption of E122, E124, and Cr(VI) follows pseudo-2nd-order kinetic and Langmuir isotherm models due to the more subordinate error functions and increased correlation coefficient (R2 ≥ 0.999). Thermodynamic studies indicate the adsorption of E122 and E124, as well as Cr(VI) ions, by CELL@HBH adsorbent to be exothermic and spontaneous. DFT calculations were employed to verify the molecular structure, analysis of Frontier Molecular Orbitals (FMOs), molecular electrostatic potential (MEP), and geometry reactivity descriptors (GRDs) for all phases. The prepared adsorbent effectively removed E122, E124, and Cr(VI) from polluted water samples, synthetic mixtures, and colored soft drinks, with a recovery rate of ~ 97%. The CELL@HBH adsorbent has good recycling performance. Under five regeneration and adsorption cycles, it still has removal effect greater than 85% of E122, E124, and Cr(VI), which indicates its high structural stability. The adsorption mechanism of E122, E124, and Cr(VI) onto CELL@HBH adsorbent is elucidated. Ultimately, this study demonstrates that the fast-responsive CELL@HBH adsorbent can be effectively utilized to eliminate E122, E124, and Cr(VI) from a wide range of real water sources. Collectively, the results indicate that the as-prepared CELL@HBH adsorbent is promising for anionic pollutant adsorption and our mechanistic results are of guiding significance in environmental cleanup. This work contributes significantly to understanding how experimental conditions influence the mechanism of E122, E124, and Cr(VI) adsorption by CELL@HBH adsorbent, offering valuable and new insights for future applications and optimizations in the treatment of effluent-containing anionic species.